Warisan konflik Indonesia-Malaysia 1963-1966: Dampaknya terhadap diplomasi masa kini - Bella, Ananda Putri Salsa; Sapto, Ari; Wijaya, Daya Negeri (LP2M Universitas Sarjanawiyata Tamansiswa, 2025)
This study aims to examine the impact of the Indonesia-Malaysia confrontation on their current diplomatic relations. The ups and downs of political dynamics are an interesting topic in examining the long-standing bilateral history. This study attempts to present perspectives from various parties as a form of objective narrative. The research method used is the historical method with a descriptive qualitative approach, through five stages: selecting the topic, which is the dynamics and impact of the Indonesia-Malaysia confrontation on their diplomatic relations; collecting sources or heuristics in the form of primary and secondary sources according to the topic; historical criticism or verification; analysis or interpretation; and historical writing or historiography. Furthermore, an in-depth analysis was conducted using a descriptive qualitative approach to obtain accurate and factual data. The results of the study indicate that the Indonesia-Malaysia confrontation had a significant impact on the political dynamics between the two countries, namely a relationship that continued to experience recurring patterns of cooperation and conflict. This confrontation has shaped the perspectives of various parties, including Indonesia, Malaysia, the United Kingdom, and the United States. Each country has a different viewpoint regarding the main actors that triggered the tension between these two neighboring countries. Although the post-confrontation period was marked by instability, diplomatic relations between Indonesia and Malaysia have gradually improved and strengthened in recent years through cultural diplomacy.